Pelayanan Pusat Kesehatan Masyarakat Di Distrik Klamono Kabupaten Sorong Provinsi Papua Barat - Christin Dessy Sahudege; Joyce J. Rares; Deysi Livy Natalia Tampongangoy (AGRI-SOSIOEKONOMI, 2022)
This study aims to describe and explain the Community Health Center Services in Klamono District, Sorong Regency, West Papua Province. The study was conducted at the Klamono Public Health Center in Klamono District, Sorong Regency, West Papua Province. The research method used is descriptive qualitative method to describe and explain phenomena that occur naturally and as they are. The informants in this study were medical personnel, namely, 1 head of the Klamono Public Health Center, 1 Head of Pharmacy / Pharmacy Room, 2 nurses (1 nurse and 1 midwife), 3 community health center employees, and also elements of the community, namely 5 people/patients who had get service. The data used in this study are primary data obtained from direct observations in the field, interviews with research informants, and documentation, while secondary data obtained from organizational structures, archival data, documents, reports and books. The technique used in data analysis in this research is interactive analysis. The results of the research conducted using the views of eight research indicators indicate that the services at the Klamono Public Health Center are already good so that it can be said to be maximal, but there are also things that are not yet good so it can be said that they are not optimal.